The private sector could play a much bigger role in promoting gender-responsive climate-smart agriculture - Muneri, Eunice Wangari (CGIAR GENDER Impact Platform, 2023)
The private sector can significantly boost women’s engagement in climate-smart agriculture by providing gender-responsive essential inputs, services and products across the agricultural value chain. The private sector’s engagement in promoting gender-responsive climate-smart agriculture has largely been short-term and not integrated into core strategies and operations. Identifying and overcoming barriers to private-sector engagement with gender-responsive climate-smart agriculture interventions can increase profitability, reduce gender inequality, and promote the goals of climate-smart agriculture (productivity, adaptation, mitigation).